The JCT intermediate building contracts 2005 - Chappell, David (David M.); Chappell, David (Oxford ; Malden, MA : Blackwell, 2006)
Chappell: The JCT Intermediate Building Contracts 2005 - Front Jacket FlapThis book provides a practical tool for all those using the suite of JCT Intermediate Building Contracts. It deals with the form under topics, considering the roles of the various parties and important matters such as payments, claims, termination and dispute resolution. Legal language has been avoided in favour of simple explanations of legal concepts, supported by flowcharts, tables and sample letters. The Third Edition has been substantially revised to take account of the 2005 versions of the mai.
8.4 Work not forming part of the contract8.5 Third party rights and collateral warranties; 8.6 Summary; Chapter 9: Possession, Practical Completion and Defects Liability; 9.1 Possession; 9.1.1 General; 9.1.2 Date for possession; 9.2 Practical completion; 9.2.1 Definition; 9.2.2 Consequences; 9.2.3 Partial possession and sectional completion; 9.3 Rectification period; 9.3.1 Definition; 9.3.2 Defects, shrinkages or other faults; 9.3.3 Frost; 9.3.4 Procedure; 9.4 Summary; Chapter 10: Claims; 10.1 General; 10.2 Extension of time; 10.2.1 Legal principles; 10.2.2 Liquidated damages.
Revised edition of: JCT intermediate form of contract. 1999.
Includes indexes.
Print version record.
John Wiley and Sons
Keywords: Construction contracts -- Great Britain; LAW -- Military; Construction contracts; Great Britain